The Influence of Reading Interest on the Ability of Writing Exposition Texts of High School Students - Pratiwi, Regi; Mayrita, Hastari (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
The purpose of this study was to determine the effect of interest in reading on the ability to write exposition texts of class X students of SMA Negeri 1 Tulung Selapan based on students' perceptions. The method used in this study is a quantitative method with a causality approach. Collecting data in this study using a questionnaire. The data in this research utilizes primary data, which is obtained directly from its source in the form of respondents' answers. The data source consists of students' perceptions regarding their reading interests and their impact on their ability to write expository texts. The population of this study was class X students of SMA Negeri 1 Tulung Selapan. Sampling was carried out using a purposive sampling technique. The sample for this research was 60 students of class X Science 1 and class X Science 2 of SMA Negeri 1 Tulung Selapan. The technique is to distribute a 1-5 Likert scale questionnaire. Data analysis in research includes validity testing, reliability testing, classical assumption testing, and hypothesis testing using a simple regression analysis model. The research findings show that there is an influence of interest in reading on the ability to write expository texts in class X Negeri 1 Tulung Selapan, South Sumatra. This is proven by the calculated t value of 4.460 > t table of 2.000 with a significance value of 0.00 < 0.05.